Posterior Reversible Encephalopathy Syndrome With Isolated Involving Infratentorial Structures - Ou, Shuchun; Xia, Lu; Wang, Li; Xia, Li; Zhou, Qin; Pan, Songqing (Frontiers in Neurology, 2018)
Typical neuroimaging findings of posterior reversible encephalopathy syndrome include symmetrical white matter edema in subcortical white matter of bilateral occipital and parietal lobes, although variations do occur and more and more attention is being focused upon disease of infratentorial-isolated involved posterior reversible encephalopathy syndrome. In this article, we described 1 case of posterior reversible encephalopathy syndrome with isolated infratentorial brain involvement and reviewed the literature to identify an additional 36 cases in the PubMed database. We used various search terms, such as “brainstem/cerebella/spinal posterior reversible encephalopathy syndrome”, “brainstem/cerebella/spinal reversible posterior leukoencephalopathy syndrome”, “brainstem/cerebella/spinal hypertensive encephalopathy”, “infratentorial posterior reversible encephalopathy syndrome” and “posterior reversible encephalopathy syndrome variant”. Then, we systematically analyzed the clinical and imaging characteristics of the 37 cases and found that posterior reversible encephalopathy syndrome with isolated involving infratentorial structures predominantly affect male patients compared with typical posterior reversible encephalopathy syndrome. The presence of extremely high blood pressure at onset is essential to the development of infratentorial-isolated involved posterior reversible encephalopathy syndrome. A relatively high rate of hydrocephalus and spinal cord involvement can be a distinctive feature of this kind of variant. Symptoms and outcomes are basically similar to typical posterior reversible encephalopathy syndrome.